Formação de professores de Física: problematizando ações governamentais - Nilson Marcos Dias Garcia; Ivanilda Higa (Universidade Estadual Paulista Júlio de Mesquita Filho, 2012)
This paper addresses current issues that have concerned Physics Teaching researchers, particularly with regard to teachers' education, from the perspective of theoretical and political aspects. Starting from reflections about the current conjuncture of educational policies and the meaning of being a teacher nowadays, the paper analyzes some public actions and policies implemented by the Brazilian Culture and Education Ministry (MEC), whose conceptions imply directly in teachers' education, in a context driven by the high demand for Physics teachers. Some reflections about the Institutional Program for Teaching Initiation Scholarships (PIBID) are performed, as well as about the policies to implement undergraduate teaching degrees in the Federal Institutes of Education, Science and Technology (IFs) as teachers' education institutions. This analysis considers the implications of such processes for teachers' education in general, and Physics teachers' education in particular. The analyses are carried out based on the legal documents which regulate such actions, seeking to reveal conceptions about teacher's education. It also intends to understand how these proposals were build, and to which extent civil society and its organizations participated in the process, trying to interpret the meaning of facing challenges that, sometimes, can mask the actual field where the disputes should or should have been held - in other words, the parliamentary and other governmental decision spheres.